A-Z Analisis Faktor-Faktor Yang Mempengaruhi Peran Perawat Dalam Menjalankan Sasaran Keselamatan Pasien - Gani, Martinus Satya; Arso, Septo Pawelas; Dwiantoro, Luky (State Islamic University of Sunan Ampel, 2024)
Patient safety is a global and national issue for hospitals, which is also an important component of the basic principles of patient care, quality of health services and a critical component of quality management. The implementation of nursing actions must be by operational standards and safety targets, to improve the quality and quality of services and minimize the number of patient safety incidents. This research aims to analyze behavioral factors that influence the role of nurses in implementing patient safety goals. This research is quantitative research with a type of non-experimental research, namely design or relationship design or to test the significance of hypotheses. Sampling in this study used the sample census method, therefore 68 nurses were selected with the criteria of 23 nurses as a profession, 1 person with a bachelor's degree in nursing, and 44 people with a D3 nursing degree. The results of this research show that the factors that influence nurses in implementing patient safety targets consist of nurse experience, age, knowledge, self-efficacy, health facilities, training and work environment. The variables of nurse experience and nurse age were not found to have a relationship with the nurse's role, but the variables of nurse knowledge, self-efficacy, health facilitation, training and work environment partially had a relationship with the nurse's role in implementing safety targets for patients at RSU William Booth Semarang. Apart from that, the results showed that the dominant factor influencing the role of nurses in implementing patient safety targets was self-efficacy.